Sulphur fertilization in groundnut crop in India: SULPHUR FERTILIZATION IN GROUNDNUT CROP IN INDIA - A SOLAIMALAI; M JAYAKUMAR; K BASKAR; M SENTHILKUMAR (Journal of Oilseeds Research, 2020)
Balanced nutrition is considered as one of the basic needs to achieve the potential yield. Sulphur is one of the major plant nutrients for that is deficient in most of the Indian soils. Sulphur is now recognized as the fourth major plant nutrient after N, P and K and is also an integral part of the balanced fertilization and nutrition for oilseed crops in general and groundnut in particular. Optimization of mineral nutrition is also a key factor to enhance productivity of groundnut. Oilseeds are energy rich crops and hence the requirement of major as well as secondary and micro nutrients is high. Sulphur is an essential plants nutrient with a specific role in the synthesis of sulphur containing amino acidslike methionine and cysteine and synthesis of proteins, chlorophyll besides oil. It promotes proper filling of grains in oilseeds and thus enhances market quality. Sulphur is also known to promote nodulation in legumes there by N fixation.Global reports of sulphur deficiency and consequent crop response, particularly in an oilseed crop like groundnut are quite ostensible. Literature with respect to the effect of sulphur application in groundnut cultivation in India has been reviewed here.